Emerging soft turn in China’s energy security cooperation with Southeast Asia - Gong, Xue (2022)
Energy security has been the paramount concern of Chinese top leaders. Geographically, Southeast Asia holds the key to China’s energy security, given its importance to Beijing’s seaborne energy trade. erefore, China’s energy cooperation in the region is o en analyzed from a hard security perspective. In a departure from these approaches, this paper explores the so er angle of China’s e ort of strengthening relations with its neighbors and assesses its impact. e so approach puts a greater emphasis on public good provision such as sustainable development instead of the old method of enhancing energy security through resource trade. The aim of this turn was to bolster trust between China and Southeast Asia, strengthen the foundations of cooperation, and improve Beijing’s image in the region. By providing a perspective di erent from hard security analysis, we shed light on the enabling and constraining factors of China’s more active role in regional energy governance.